2020
DOI: 10.1155/2020/2948282
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Predominant Fecal Microbiota and Disruption of the Gut Mucosal Barrier in Patients with Early-Stage Colorectal Cancer

Abstract: Growing evidence indicated that the gut microbiota was the intrinsic and essential component of the cancer microenvironment, which played vital roles in the development and progression of colorectal cancer (CRC). In our present study, we investigated the alterations of fecal abundant microbiota with real-time quantitative PCR and the changes of indicators of gut mucosal barrier from 53 early-stage CRC patients and 45 matched healthy controls. We found that the traditional beneficial bacteria such as Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…Fusobacterium nucleatum (F. nucleatum) is enriched in human colorectal adenomas and carcinomas (45,57) and may contribute to disease progression from adenoma to cancer (46). In our recent study, F. nucleatum was significantly increased in patients with early-stage CRC (49). The presence of F. nucleatum in CRC tissues indicated a worse prognosis (47,48).…”
Section: Intestinal Microbiota In Crcmentioning
confidence: 98%
“…Fusobacterium nucleatum (F. nucleatum) is enriched in human colorectal adenomas and carcinomas (45,57) and may contribute to disease progression from adenoma to cancer (46). In our recent study, F. nucleatum was significantly increased in patients with early-stage CRC (49). The presence of F. nucleatum in CRC tissues indicated a worse prognosis (47,48).…”
Section: Intestinal Microbiota In Crcmentioning
confidence: 98%
“…Protein & (Xie et al, 2017) Gut microbiota in CRC and HCC producers (i.e., Lachnospira multipara and Eubacterium eligens) and Bifidobacterium longum were depleted with the progression of CRC. Like HCC, there are changes in the composition of the microbiota as the disease progresses through different stages (Liu et al, 2020).…”
Section: Reviewmentioning
confidence: 99%
“…In seven studies, cases and controls were matched for two to four variables, including age, gender, body mass index, ethnicity, and the time period of sample collection [42,47,50,51,53,54,57,62]. There were 13 studies that excluded subjects with reported antibiotic use in the last month, or in the last 3 months or 6 months, and 11 studies that excluded patients previously diagnosed with IBD.…”
Section: Characteristics Of Studies Included In the Systematic Reviewmentioning
confidence: 99%